Enhancing Financial Literacy to Promote Sustainability in MSMEs - Puspita, Vina Anggilia; Rinaldo, Dito; Gunardi, Gunardi (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
This study seeks to determine the influence of financial literacy on the sustainability of MSME enterprises. The research is based on the phenomenon of poor business sustainability in Indonesian MSMEs. Using interviews and a survey of 400 respondents, this study discovered that MSME owners' financial literacy remains low, which contributes to poor business financial management and has a substantial influence on firm sustainability. The regression test results show that there is a significant positive influence of the level of financial literacy on the sustainability of MSME businesses. This indicates the necessity for various parties to cooperate in providing substantial education on financial literacy to MSMEs to sustain and develop. Keywords: Entrepreneurship; Financial Governance; Financial Literacy; Business Sustainability; MSMEs